Pengembangan E-Modul Literasi Numerasi Aljabar Siswa Sekolah Menengah Pertama - Nuralam Syamsuddin; Siti Salamah Manik; Khusnul Safrina (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2024)
Numeracy literacy skills are crucial for students, yet data from PISA and TIMSS indicate that Indonesian students' proficiency in this area remains low. Numeracy literacy teaching materials are lacking, with most teachers still using conventional methods. Therefore, innovation is needed in developing teaching materials. This research aims to develop an electronic numeracy literacy module on linear function material for Grade VIII SMP that meets validity and practicality standards. The ADDIE method (Analysis, Design, Develop, Implement, Evaluate) is used for development, with Grade VIII students from SMPN 2 Banda Aceh as the research subjects. Data collection instruments include interviews, validation sheets, student response questionnaires, and teacher feedback. Data are then analyzed descriptively, in percentages, and qualitatively. The research results indicate that the developed product has passed the material validation stage with a result of 91.74%, indicating high material validity. Media validation also succeeded with a percentage of 90.48%, showing very high validity levels. The practicality test conducted with teachers yielded a result of 88.33%, indicating the practicality of the e-module in teaching. Meanwhile, the practicality test with students resulted in a score of 84.56%, indicating that this e-module is also practical for students. Overall, the e-module developed in this research has proven to be valid and practical for use in school learning.